Effectiveness of paramedic practitioners in attending 999 calls from elderly people in the community: cluster randomised controlled trial. Issue 7626 (4th October 2007) - Mason, Suzanne; Knowles, Emma; Colwell, Brigitte; Dixon, Simon; Wardrope, Jim; Gorringe, Robert; Snooks, Helen; Perrin, Julie; Nicholl, Jon
Abstract : Objective To evaluate the benefits of paramedic practitioners assessing and, when possible, treating older people in the community after minor injury or illness. Paramedic practitioners have been trained with extended skills to assess, treat, and discharge older patients with minor acute conditions in the community. Design Cluster randomised controlled trial involving 56 clusters. Weeks were randomised to the paramedic practitioner service being active (intervention) or inactive (control) when the standard 999 service was available. Setting A large urban area in England. Participants 3018 patients aged over 60 who called the emergency services (n=1549 intervention, n=1469 control). Main outcome measures Emergency department attendance or hospital admission between 0 and 28 days; interval from time of call to time of discharge; patients' satisfaction with the service received. Results Overall, patients in the intervention group were less likely to attend an emergency department (relative risk 0.72, 95% confidence interval 0.68 to 0.75) or require hospital admission within 28 days (0.87, 0.81 to 0.94) and experienced a shorter total episode time (235 v 278 minutes, 95% confidence interval for difference −60 minutes to −25 minutes). Patients in the intervention group were more likely to report being highly satisfied with their healthcare episode (relative risk 1.16, 1.09 to 1.23). There was no significant difference in 28 day mortality (0.87, 0.63 to 1.21). Conclusions Paramedics with extended skills can provide a clinically effective alternative to standard ambulance transfer and treatment in an emergency department for elderly patients with acute minor conditions. Trial registration ISRCTN27796329 .